Educação da criança de zero a três anos e educação especial: Uma leitura crítica dos documentos que norteiam a educação básica - De Vitta, Fabiana Cristina Frigieri [UNESP]; Da Silva, Carla Cilene Baptista; Zaniolo, Leandro Osni [UNESP] (FapUNIFESP (SciELO), 2016)
Nursery schools that offer quality education have an important role in promoting the development of 0-to-3- year-old children. The nursery school, as part of preschool education, must incorporate special education, providing educational opportunities to children with disabilities, global developmental disorders and giftedness. After a critical analysis of official documents that guide preschool education, we aimed to answer to the following questions: how is the nursery school portrayed and treated in these documents? Have they secured special education services at this stage? What kind of contributions are still needed for education in nursery schools to be efficient to all children? We verify the absence of references to the 0-to-3 year-old group and special education service. There are several factors which contribute to the quality of early childhood education that promote education for all, such as conceptual factors, physical, human and material resources. There is a need to discuss the role of nursery schools and special education at this stage, ensuring presumptions aimed to provide integral development for all children.
Zero-to-three-year-old children education and special education: A critical analysis of documents guiding preschool education
Keywords: Especial Education; Nursery School; Preschool Education; Public Policies